In Search of Chronology: Narratives of Qur’anic Evolution in Western Academia 1 - Emmanuelle Stefanidis (ReOrient)
Since the nineteenth century, Orientalist scholars have been preoccupied with recovering the original order of the Qur’an. In the past fifty years, the question appears to have reached an impasse with no sign of an emerging consensus. Divergences over the anchoring in space and time of the Qur’an have contributed to the diagnosis of “crisis” in (Western) Qur’anic studies. What do the project of determining Qur’anic chronology and its failure tell us about Qur’anic studies in Western academia? What do the current impasses reveal about the nature of the Qur’an as a text and as a theological object? This study analyses disagreements over the Qur’an’s space and time by drawing on tools from literary theory and hermeneutics. It argues for a shift from a positivist to an interpretative paradigm. Moving away from the question of the actual historical order of the Qur’an, this article examines the making and the workings of diachronic readings of the Muslim scripture, with a particular focus on the works of two of the most prominent scholars in the field, Angelika Neuwirth and Nicolai Sinai. The aim of the exercise is double: first, to perform a critical reflection on the networks of meaning that we construct or inherit in our engagement with the Muslim scripture; and second, to apprehend better the nature of the Qur’an as an “open text” (Eco 1962) whose textual characteristics make it particularly prone to a number of interpretations.